Relationship Between Healthy Organisational Resources and Organisational Citizenship Behaviour of Employees in an Institution of Higher Education - Braian López; Leonardo De Pablos; Mabel Ibarra (Ianna Journal of Interdisciplinary Studies)
Background: Healthy organisational practices proposed by the Healthy and Resilient Organisations (HERO) model were used as independent variables to analyse people management in the organisation. These practices influenced workers´ health and well-being, measured by engagement as a positive practice and burnout as a negative practice.